Day Case Laparoscopic Anti–reflux Surgery - Kaundinya Kiran Bharatam (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
As day care surgeries become more common, we always need to choose patients and procedures within a great deal of safety margin. Anti-reflux surgeries are gaining more popularity and awareness and Laparoscopic Nissen Rosetti fundoplication is a safe and effective method of performing them. We present a case series of 25 patients who underwent day care Laparoscopic Nissen Rossetti fundoplication done over a period of 3 years suggests the feasibility and safety of performing day care anti reflux surgeries with no complications. Surgical outcomes of procedure are unaffected, and the main challenge faced remains pain relief and which can be effectively tackled by local nerve blocks or NSAIDs. Laparoscopic Nissen Rossetti fundoplication is a safe procedure to be offered as day care anti- reflux surgery.